استخدام وسائل نص القصة لترقية مهارة القراءة : (دراسة إجرائية في نور الرشاد العزيزية سجلي) - Syarifah Rahmi (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The objectives of this research are to know the process of teaching the reading skill before applying the means of story text in the private Islamic middle school Nour Al-Rashad Al-Aziziyah my record, and to find out the effectiveness of using the story text means to upgrade the reading skill in the private Islamic middle school Nour Al-Rashad Al-Aziziyah. The research method that the researcher used was the procedural research method. To collect the data, the researcher observed and presented the pre- and post-test. As for the results of the research, it was the process of teaching and learning the reading skill, in agreement with the steps of applying the means of the story text and its steps. The teacher chooses the subject of the educational materials, such as reading texts, which he may cut with a piece of paper, as well as the total number of students, and the use of the means of the story text in the process of teaching and learning the reading skill was effective and constructive on the average score of the students.